South Asian Arms Control in Perspective of US-Soviet Experience - Saima Aman Sial; Mr. Muhammad Sarmad Zia (CISS Insight Journal, 2017)
The advent of nuclear weapons in South Asia changed the dynamics of the relationship between India and Pakistan: adding a new dimension to their complex and adversarial relationship. The unsettled disputes left behind as a legacy of the unfinished agenda of the partition still haunt the bilateral relations. Both India and Pakistan have fought two wars, and since nuclearization have been through four military crises, bringing them near the brink of conflict/war. Moreover, the acquisition and development of new weapon systems, capabilities and doctrines that undermine deterrence are also a common denominator of their competition, increasing the chances of accidental or unauthorized use of nuclear weapons. The situation is one which demands that measures to control this competition should be put in place and efforts to develop and build mutual confidence to decrease their mutual anxieties should be enhanced. Whereas, it should be logical to see both states sharing the common interest in pursuing arms control to address their mutual anxieties and develop common understanding on issues of mutual discord, reduce the likelihood of conflict, crisis and miscalculation; the practical situation poses a dilemma.